Assessing Pedagogical Innovations: Empowering Excellence with OSVE in Undergraduate MBBS Students at Rai Medical College,Sargodha - Mudaser hussain Abbasi; Kamran Arzoo; Muhammad Hammad Jatalla; Sundas Ahmad; Tanveer ZIa Qureshi; Zahid Masood (Aziz Fatimah Medical and Dental College, 2024)
Objectives: To explores the perception & effectiveness of objectively structured viva examinations (OSVE) in 3rd year MBBS students as compared to routine general viva for future implementation at Rai Medical College, Sargodha. Methodology: This cross-sectional study was performed at Rai Medical College (RMC), Sargodha The total number of participants were 120 third-year MBBS students.Routine objectively structured viva examinations (OSVE) of forensic medicine was conducted. During the OSVE, each student was assigned to specific stations. The students' viewpoints were evaluated before and after the OSVE through a customize structured questionnaire.Categorical variables including the responses strongly agree, agree, neutral, strongly disagree, disagree are presented as frequencies and percentages. Chi square test was used to check the differences in proportions of perception of male and female concerning various aspects of OSVE. Results:  This study was comprised of 120 medical students, of which 65(54.16%) and 55(45.93%) were female and male student respectively. Of total participants 39.2 and 25% of students were felt that structured viva format was more convenient than routine unstructured viva. Of total students 47.5 % of students agreed that the allocated time for answering questions in OSVE was appropriate. Concerning encouragement from teacher to give relevant answer during OSVE, 48.3 % and 45.0% of students were strongly disagreed and disagreed respectively rest were agreed or remain neutral. Only19.2 and 23.3% of students were strongly agreed and agreed presence of bias in unstructured oral viva. Most of students were strongly agreed (37.5 %) or agreed (29.2%) for implementation of OSVE for all academic years for all medical subjects. Significant statistical difference was observed in opinions of male and female with respect to encouragement in OSVE from examiner and biasness during unstructured viva with p values0.002 and 0.027, whereas we did not find any significant difference among gender point of views for all other aspects of OSVE. Conclusion: Objectively structured viva examinations, as perceived by the participants, was mostly convenient and bias free mode of assessment compared to traditional unstructured oral viva examination.  OSVE should be implemented in all academic years for all subjects.